Genetic improvement of indigenous cattle for milk and draught: A review - Joshi, B K; Singh, Avtar; Mukherjee, S (The Indian Journal of Animal Sciences, 2005)
The present review attempts to assess the perfomance potential of various digenouscattle breeds with respect to growth, reproduction, milk production and draught. The estimates of genetic parameters and genetic progress over time have been presented from the organized herds and limitations of the genetic parameters in terms ofpoor precision and the causes of genetic deterioration in most of the closed herds of indigenous cattle breeds have been identified. Comprehensive documentation by conducting the field surveys to develop breed descriptors in thc native ecology (production system) and identification of unique and true breeding populations coupled with socio-economic condition of the farmer has been suggested. The imperative need for breed-wise cattle census and field recording has been highlighted. The urgency to strengthen the breed societies and herd registration schemes to cover almost every descript breed with field recording on a larger population linked to breed improvement programmes has been stressed. It has been suggested that the breedspecific government and private organized farms and progressive farmers/breeders maintaining relatively large herds should be associated to form a sizable test herd population for evaluating a large number of breeding bulls and necessary infrastructure for providing breeding facilities, performance recording and evaluation of village herds should be developed. In the absence of field recording, Open Nucleus Breeding system (ONBS) with or without MOET for production and evaluation of young bulls and for augmenting the genetic gain has been suggested. Upgrading non-descript populations with descript improver breeds from the same region to enhance milk production and draughtability has been underlined. The need for a true long-term economic evaluation of cattle genetic resources; particularly comparing locally adapted and exotic/crossbred genotypes in the same production systems based on their utility (milk or draught or both) has been emphasized. Innovations in subsistence cattle farming must bedeveloped and tested to ensure that they produce sustainable benefits. The need for studying the genetics of draughtability and the relationship between draughtability and milk production so as to develop strategy for improvement of both milk and draught in an optimal manner has been emphasized. In future, marker assisted selection of animals seems to be apossibility for helping to locate particular genes with major effects on milk production/draught and may act as an aid to progeny testing of sires.